Peningkatan Keterampilan Proses Sains Peserta Didik Melalui Simulasi Phet Listrik dengan Model Discovery Learning - Nurfaida, Nurfaida; Haris, Abdul; Ariani, Ariani (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This classroom action research aims to enhance the science process skills of students at SMA 22 Gowa through the use of PhET Electricity simulations with a discovery learning model. The research is conducted in two cycles, with the participation of students from class XII MIPA 1 as the research subjects. Each cycle consists of planning, implementation, observation, and reflection, focusing on the development of science process skills. During the research, students were given access to PhET Electricity simulations, allowing them to conduct virtual experiments and interactively observe concepts of static and dynamic electrical physics. The results of the research show a significant improvement in the science process skills of students after implementing the simulation. They demonstrated improvement in the ability to identify variables, formulate hypotheses, plan experiments, predict, communicate, and interpret data. PhET Electricity simulations based on discovery learning can enhance the science process skills of students in the second cycle. Keywords: discovery learning, science process skills, PhET electricity simulation